Health care workers and migrant health: Pre- and post-COVID-19 considerations for reviewing and expanding the research agenda - Virginia Gunn, PhD; Rozina Somani, PhD Candidate; Carles Muntaner, PhD (Elsevier, 2021)
The main purpose of this article is to review several ways in which health care workers could either impact migrant health or be directly impacted by migration and, based on this, suggest the expansion of the current research agenda on migration and health to address a range of topics that are currently either neglected, insufficiently researched, or researched from different perspectives. To ground this suggestion and emphasize the complexity and significance of migrant health research, we start by briefly reviewing several migration-related notions including the process of migration and its key facilitators and benefits; existing barriers to the provision of migrant health care; and the intricate links between health systems, health professionals, and migrant health.The three areas of research examined in this article address (i) the specific role of health workers in providing care to migrants and refugees and their capacity to do so, (ii) the health problems experienced by health workers who become migrants or refugees, and (iii) the precarious employment conditions experienced by both migrant and non-migrant health care workers. After summarizing the current available evidence on these topics, we discuss key information gaps and strategies to address them, while also incorporating several relevant COVID-19 pandemic considerations and research implications.Expanding the focus of research studies on migration and health could not only enhance the results of current strategies by supplying additional information to support their implementation but also spearhead the development of new solutions to the migrant health problem.